High resolution topobathymetry using a Pleiades-1 triplet: Moorea Island in 3D - Collin, Antoine; Hench, James L.; Pastol, Yves; Planes, Serge; Thiault, Lauric; Schmitt, Russell J.; Holbrook, Sally J.; Davies, Neil; Troyer, Matthias (Remote sensing of environment, 2018)
Worldwide the coastal land-sea interface is increasingly subject to natural and anthropogenic hazards. Monitoring this crucial interface may be addressed with satellite imagery as a cost-efficient mapping solution. Topography and bathymetry, defining the structural complexity of the coast, are commonly studied separately given specific thematic and methodological contexts, yet many science questions and societal challenges require an integrated approach (e.g., coastal inundation). In such cases, triplet multispectral imagery represents an affordable solution based on a single satellite product. Here we examine how Pleiades-1 triplet imagery may be used to retrieve a seamless and accurate topobathymetry digital surface model (DSM, from −20 to 1207 m) over an entire, socio-ecologically complex island: Moorea, French Polynesia. Creation of the topography DSMs was based on stereo and tri-stereo photogrammetry, and the bathymetry DSMs relied on quasi-nadiral multispectral data subject to light/water interaction modelling. Results were compared with over 3.9 million airborne LiDAR topobathymetry measurements to quantify how the spatio-spectral mode, the third imagery, and the level of radiometric correction act on two- and three-dimensional accuracy. Horizontal accuracy of the tri-stereo panchromatic dataset (ERMSE = 4.22 and NRMSE = 7.59 m) was better than the multispectral (ERMSE = 5.06 and NRMSE = 7.51 m) dataset. Topography point cloud density increased by a factor of three in the tri-stereo panchromatic (9.11 points/m2) or multispectral (0.23 points/m2) datasets. Topography vertical accuracy enhanced with tri-stereo + level-1 radiometric correction (RMSE = 7.40 m) for panchromatic and with stereo + level-1/-2 radiometric correction (RMSE = 7.77/7.77 m) as well as tri-stereo without radiometric correction (RMSE = 7.85 m) for multispectral datasets. Bathymetry vertical accuracy improved with level-2 (atmospheric) correction (RMSE = 0.83 m). Topobathymetry DSM derived from this optimized method has a wide spectrum of applications along coastal margins. [Display omitted] •High spatial resolution topobathymetry of Moorea Island is investigated.•Pleiades-1 triplet imagery extracts topography and bathymetry digital surface models.•Panchromatic tri-stereo TOA reflectance gives best topography accuracy (RMSE = 7.49 m).•Multispectral mono DOA reflectance provides best bathymetry accuracy (RMSE = 0.88 m).•A single triplet Pleiades-1 imagery models seamless structure of coastal habitats.